STUDI ANALISIS PEMAHAMAN JAMAAH TABLIGH DALAM PENGKAJIAN HADIS NABI DI KOTA PALU SULAWESI TENGAH - Kamridah dan Suraya Attamimi (Program Studi Ilmu Al-Qur'an dan Tafsir, Institut Agama Islam Negeri (IAIN) Palu, 2021)
This paper analyzes the use of the study of the hadith of the Prophet saw in each da'wah delivered. one of the cases is the activities of the Tabligh congregation in the mosque there is usually a study of hadith held after morning deliberation, meal break, charity infirady (personal) from 9 to 12 o'clock after that recite the Qur'an fadhilah, prayer fadhilah, dhikr fadhilah and alms tabligh, fadhilah ramadhan (in the month of Ramadhan) and fadhilah haji (in the month of dzulhijjah/month of hajj). This is a special study for researchers related to the hadiths used in his preaching. As well as its implementation in everyday life. In the search, the researcher of Jamaah Tabligh understood the hadith textually in accordance with what is contained in the hadith. So that sometimes it seems very textual and goes back to the time of the Prophet. For example the hadith of preserving the beard is understood not to shave the beard. The method used by researchers in analyzing the hadith is the method of takhrij Hadith which is reviewed from various books and tracked by each narrator.